The Effect of the Contextual Learning Model on Ninth-Grade Students’ Learning Outcomes in Solid Geometry at SMP Negeri 17 Malang - Zainul Rohman; Zainul Abidin; Otto Fajarianto (Teknologi Pendidikan ID, 2026)
This study was motivated by students’ low achievement in solid geometry, which was attributed to the subject matter’s lack of relevance to students’ daily lives. Contextual learning is a student-centered approach that develops students’ intellectual potential to construct knowledge and then give meaning to that knowledge. This study aims to determine the effect of the contextual learning model on the cognitive learning outcomes of ninth-grade students at SMP Negeri 17 Malang. The research method used was a quasi-experimental design with a non-equivalent pretest-posttest control group. The research sample, selected through purposive sampling, consisted of two groups: Class IX A and Class IX C. The research instrument consisted of multiple-choice questions designed to measure student learning outcomes. The results showed that the post-test scores of the experimental group increased significantly compared to the control group, with a significance level of 0.029 < 0.050 in the t-test, meaning H0 was rejected and H1 was accepted. These findings indicate that learning that connects subject matter to students’ real-world contexts can enhance their application skills, thereby influencing their learning outcomes regarding spatial concepts. These research results confirm that the contextual learning model is proven to be effective in improving student learning outcomes.